Complications in the Management of Acute Achilles Tendon Rupture: A Systematic Review and Network Meta-analysis of 2060 Patients. Issue 9 (July 2019) - Wu, Yahong; Mu, Yuan; Yin, Liangjun; Wang, Zhuoqun; Liu, Wenke; Wan, Haimin
Background: Acute Achilles tendon rupture (ATR) has increased in the past decade, and many new treatments and rehabilitation regimens have been introduced. But major complications in ATR management remain an unsolved problem. Purpose: To compare the risk of major complications of acute ATR after different combinations of treatments and rehabilitation regimens. Study Design: Systematic review and network meta-analysis. Method: The authors searched 4 databases (PubMed, Medline, Embase, and the Cochrane Library) from the date of inception until February 2018 for articles in English. The authors considered randomized controlled trials comparing interventions and rehabilitation protocols for acute ATR and restricted (1) interventions to nonoperative treatment, minimally invasive surgery, and open surgery and (2) rehabilitation protocols to accelerated rehabilitation and early immobilization. Major complications were assessed—namely, rerupture, deep infection, and deep vein thrombosis (DVT). Only patients with primary acute ATR were considered. Quality assessment was performed with the Cochrane "risk of bias" tool. A series of additional tests were conducted to ensure the validity of the results. Results: Twenty-nine randomized controlled trials with 2060 patients were included in this Bayesian network meta-analysis. The mean incidence of overall major complications from all managements was 9.13% (median, 6.67%). The mean incidence rates of rerupture, deep infection, and DVT from all managements were 5%, 1.50%, and 2.67%, respectively. According to relative risk, nonoperative treatment combined with early immobilization was significantly associated with a higher risk of major complications. According to the surface under the cumulative ranking curve, minimally invasive surgery with accelerated rehabilitation had the highest possibility (79.7%) of being the best management with regard to minimizing major complications. Conclusion: For treating acute ATR, management combining minimally invasive surgery with accelerated rehabilitation had the highest possibility of being superior in terms of major complication risks, according to the surface under the cumulative ranking curve. Management combining nonoperative treatment with early immobilization was statistically associated with a higher risk of complications as compared with the other methods of management.